Youth Unemployment in Europe: What to Do about It? - Werner Eichhorst; Holger Hinte; Ulf Rinne (Institute for the Study of Labor (IZA), 2013)
Youth unemployment has become a severe economic and societal problem in many European countries. This paper gives an overview of the current situation and assesses different policy options. It emphasizes the role of stronger intra-EU mobility of young workers, policies to make vocational training systems more effective and to adjust employment protection as well as activating labor market policies. However, short-term remedies are not available, despite the fact that the EU has announced massive European initiatives. Rather, European countries should take the opportunity of the crisis to implement forward-looking structural reforms.
Keywords: J24; J64; J13; 330; fixed-term contracts; Europe; vocational training; youth unemployment; Jugendarbeitslosigkeit; Berufsbildungspolitik; Arbeitsmigranten; Aktivierende Arbeitsmarktpolitik; EU-Staaten